PENGARUH KEPEMIMPINAN, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Agus Riyanto; Yunis Vertina Zaq (Human Capital Development, 2018)
Purpose- This study aims to determine the influence of leadership, compensation and motivation to the employee performance at Grand Paragon Jakarta. Design/methology/approach- The study of variable be consisting of the independent variable are leadership, compensation and motivation of the dependent variable about performance. Kinds of data that will be study are primary data. A population that use in this research are all of staff at Grand Paragon Hotel. Sampling technique using saturation saturate sampling technique. Data collected and then analyzed using a program SPSS Versi 24. Findings- Can be concluded about leadership have a effect signification to the employee performance because the study of leadership a much 4,47 % . compensation have a effect of signification and positif to the staff performance is 15,70 %. Based on research of leadership, compensation and motivation with all of signifation influence and positive to the employee performance with the contribution are 24,01 %, and while the rest a much 75,99 % to effect by another variable its not to